PENGARUH LANGSUNG DAN TIDAK LANGSUNG GOOD CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Sastrawan, I Made Dwi; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi; Vol 14 No 1 (2016), 2016)
This study aimed to determine whether the direct and indirect effects of good corporate governance (GCG) to corporate social responsibility (CSR) disclosure. The population of this study was the companies that listed in Indonesia Stock Exchange and followed in Corporate Governance Perception Index (CGPI) ranking conducted by The Indonesian Institute for Corporate Governance (IICG) in year 2011-2013. Sampling method used saturated sampling with a total sampel of 12 companies. Analysis technique was used is path analysis. Based on the result of the analysis found that GCG proved a direct effect on CSR  disclosure and financial performance proved incapable of mediating the effect of GCG on CSR  disclosure. The financial performance was not able to mediate the relationship between GCG on CSR disclosure because the shareholders wants to get high return without thinking the other thing such as the additional cost to disclose CSR which will lead to a competitive disadvantage.
Keywords: Good Corporate Governance, Financial Performance, Corporate Social Responsibility Disclosure